A Cytostatic Ruthenium(II)–Platinum(II) Bis(terpyridyl) Anticancer Complex That Blocks Entry into S Phase by Up‐regulating p27KIP1. Issue 25 (7th May 2015) - Ramu, Vadde; Gill, Martin R.; Jarman, Paul J.; Turton, David; Thomas, Jim A.; Das, Amitava; Smythe, Carl
Abstract Cytostatic agents that interfere with specific cellular components to prevent cancer cell growth offer an attractive alternative, or complement, to traditional cytotoxic chemotherapy. Here, we describe the synthesis and characterization of a new binuclear RuII–PtII complex [Ru(tpy)(tpypma)Pt(Cl)(DMSO)]3+ (tpy=2, 2′:6′, 2′′‐terpyridine and tpypma=4‐([2, 2′:6′, 2′′‐terpyridine]‐4′‐yl)‐N‐(pyridin‐2‐ylmethyl)aniline), VR54, which employs the extended terpyridine tpypma ligand to link the two metal centres. In cell‐free conditions, VR54 binds DNA by non‐intercalative reversible mechanisms (Kb=1.3×105 M−1) and does not irreversibly bind guanosine. Cellular studies reveal that VR54 suppresses proliferation of A2780 ovarian cancer cells with no cross‐resistance in the A2780CIS cisplatin‐resistant cell line. Through the preparation of mononuclear RuII and PtII structural derivatives it was determined that both metal centres are required for this anti‐proliferative activity. In stark contrast to cisplatin, VR54 neither activates the DNA‐damage response network nor induces significant levels of cell death. Instead, VR54 is cytostatic and inhibits cell proliferation by up‐regulating the cyclin‐dependent kinase inhibitor p27KIP1 and inhibiting retinoblastoma protein phosphorylation, which blocks entry into S phase and results in G1 cell cycle arrest. Thus, VR54 inhibits cancer cell growth by a gain of function at the G1 restriction point. This is the first metal‐coordination compound to demonstrate such activity.